2012
DOI: 10.1108/07363761211274983
|View full text |Cite
|
Sign up to set email alerts
|

Green consumer behavior in an emerging economy: confusion, credibility, and compatibility

Abstract: PurposeThe purpose of this research is to contribute to a better understanding of deeper motivations and inhibitors of green consumer behavior in the context of emerging economies. Based on the findings, it aims to provide implications for marketers and policy making.Design/methodology/approachBased on an ethnographic approach, in‐depth interviews and observational data were used to study 15 Mexican families from four urban regions of Mexico with different incomes. Thematic analysis was used to develop and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
2
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 42 publications
5
107
2
17
Order By: Relevance
“…In emerging economies in general, some researchers have found limited sensitivity to environmental issues as a consequence of poor knowledge, high-costs, and skepticism associated with ecologically friendly products. Even when awareness existed, environmental sensitivity was limited (Carrete et al, 2012). Carrete et al (2012) also found that Mexican consumers did not engage in much green behavior and when they did, the key motivator was family well being rather than environmental sensitivity.…”
Section: Long-term Orientation (Lto)mentioning
confidence: 99%
See 1 more Smart Citation
“…In emerging economies in general, some researchers have found limited sensitivity to environmental issues as a consequence of poor knowledge, high-costs, and skepticism associated with ecologically friendly products. Even when awareness existed, environmental sensitivity was limited (Carrete et al, 2012). Carrete et al (2012) also found that Mexican consumers did not engage in much green behavior and when they did, the key motivator was family well being rather than environmental sensitivity.…”
Section: Long-term Orientation (Lto)mentioning
confidence: 99%
“…Even when awareness existed, environmental sensitivity was limited (Carrete et al, 2012). Carrete et al (2012) also found that Mexican consumers did not engage in much green behavior and when they did, the key motivator was family well being rather than environmental sensitivity. Hofstede (1980) states that long-term orientation refers to the prospects perceived by an individual that a society will be in a position to overcome its problems over time.…”
Section: Long-term Orientation (Lto)mentioning
confidence: 99%
“…The green consumer believes that the current environmental conditions represent serious problems facing the sustainability of the planet, whereas the traditional consumer who is less sensible to ecological issues believes that those environmental problems will be resolved by themselves (Carrete et al, 2012).…”
Section: Green Consumermentioning
confidence: 99%
“…O sentimento de inutilidade, impotência e sacrifício são centrais no comportamento ambientalmente responsável e, como sugere o Modelo da Pessoa Razoável (Kaplan, 2000), a ação pró-ambiental deve estar pautada em algo desejável pelo homem, em algum benefício pessoal. Se ele encontrar situações onde se enxerga uma possibilidade de atuação, como no exercício profissional, nas quais é possível enxergar também benefícios pessoais, sentimentos de impotência e sacrifício são postos de lado (Kaplan, 2000;Carrete, Castaño, Felix, Centeno, & González, 2012).…”
Section: Considerações Finaisunclassified